Estudio del estado actual para el desarrollo de un Plan de Saneamiento Ambiental para la comunidad urbana del cantón de La Unión, Cartago - Rodríguez-González, Wester (Instituto Tecnológico de Costa Rica, 2015)
The community of La Union aim to prevent and improve the quality of the environment, as it shows deficiencies in the environmental sanitation. As a first approach to analyze the problematic, the local municipality and the Tecnológico of Costa Rica are executing the project “Developing of a sanitation plan for the urban community of La Union". This research show the results of some sanitation indicators of the community: the status of the WWTP and hydrological network (rivers: Chagüite, La Cruz, Chiquito y Tiribí), besides community homes infrastructure data( separation of sewage and rain water, facilities for the sewage management, the sewage location and exits level from the street) through the respective survey. Universal parameters required for treatment plants wastewater analyzes were monitored during 2014 for 4 public WWTP and for 2015 in 18 of private management. Deficiencies such as lack of design parameters, lack of water exits to the receiving bodies, no maintenance plan, inefficient settlers, useless drying beds, and aeration systems collapsed. Monitoring of rivers in the city was performed using interest parameters for the Evaluation and Classification of the Quality of the Superficial Water Bodies and dumping analysis required, in three sampling campaigns. It is necessary to mitigate and prevent the pollution they have now, since some points are exceeding 10 mg / L BOD that the international standards set for good quality rivers which makes them unhealthy. Sewerage coverage is very low (9 %), and the willingness to connect in a future sewer, depends on the location of the water outlet of each household, and the economic costs involved. The city need for urgent intervention in environmental sanitation, sewerage construction, improvement in the wastewater treatment, and elimination of illicit connections receiving bodies if in the future the city wants to position itself as a sustainable city. Keywords: Sanitation, sewage, wastewater treatment plant, superficial water bodies.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica. Escuela de Química. Carrera de Ingeniería Ambienta,. 2015.
Keywords: Plantas de tratamiento; Saneamiento ambiental; Aguas residuales; Sostenibilidad ambiental; Saneamiento y alcantarillado; Aguas superficiales